Implementing Robust Data Governance Frameworks in the Snowflake Platform - Durga Prasad Katasani, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In the rapidly evolving digital landscape, data governance has emerged as a critical strategic imperative for organizations navigating complex technological challenges. This comprehensive exploration delves into the intricate dynamics of modern data management, focusing on platform-specific governance frameworks within the Snowflake ecosystem. By examining the intersection of advanced security architectures, innovative implementation methodologies, and integration strategies, the article illuminates the transformative potential of sophisticated data governance approaches. This article transcends traditional technological perspectives, presenting a holistic framework that addresses critical challenges such as regulatory compliance, data democratization, and security optimization. Through an in-depth analysis of role-based access control, dynamic data masking, and adaptive authentication mechanisms, the article demonstrates how organizations can develop robust, flexible governance strategies that balance operational efficiency with comprehensive information protection. The exploration reveals that effective data governance is no longer a mere technical requirement but a strategic capability that directly influences organizational innovation, competitiveness, and long-term digital resilience.
Keywords: Data Governance; Snowflake Platform; Role-Based Access Control; Security Architecture; Integration Frameworks